Exploring the Role of Matrix Metalloproteinases as Biomarkers in Sporadic Lymphangioleiomyomatosis and Tuberous Sclerosis Complex. A Pilot Study - Terraneo, Silvia; Lesma, Elena; Ancona, Silvia; Imeri, Gianluca; Palumbo, Giuseppina; Torre, Olga; Giuliani, Lisa; Centanni, Stefano; Peron, Angela; Tresoldi, Silvia; Cetrangolo, Paola; Di Marco, Fabiano (Frontiers in Medicine, 2021)
Background: Lymphangioleiomyomatosis can develop in a sporadic form (S-LAM) or in women with tuberous sclerosis complex (TSC). The matrix metalloproteinases (MMPs) are extracellular matrix-degrading enzymes potentially involved in cystic lung destruction, and in the process of migration of LAM cells. The aim of the study was to explore the role of MMP-2 and MMP-7, such as vascular endothelial growth factor (VEGF) -C and -D in women with LAM, including patients with “minimal disease” (i.e. less than 10 lung cysts), and TSC with or without LAM. Methods: we evaluated 50 patients: 13 individuals affected by S-LAM, 20 with TSC-LAM, of whom 6 with “minimal disease”, and 17 with TSC without pulmonary involvement. 16 healthy women were used as controls. Results: MMP-2 resulted higher in LAM compared to healthy volunteers, and TSC patients (p=0.040). MMP-7 was higher in TSC-LAM patient, with even greater values in patients with TSC-LAM “minimal disease”, than in S-LAM patients, and in controls (p=0.001). VEGF-D level was lower than 800 pg/mL in all healthy controls, and resulted higher in S-LAM and TSC-LAM than in TSC patients and controls (p<0.001). VEGF-C values were not statistically different in the study population (p=0.354). The area under ROC curves (AUCs) of MMP-2, and MMP-7 for predicting LAM diagnosis were of 0.756±0.079 (p=0.004), and 0.828±0.060 (p<0.001), respectively. Considering only patients with TSC, the AUCs for MMP-2, and MMP-7 in predicting LAM were 0.694±0.088 (p=0.044), and 0.713±0.090 (p=0.027), respectively. Conclusions: MMP-2 and MMP-7 could be promising biomarkers for LAM diagnosis.